2010
DOI: 10.1016/j.jaad.2009.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting nephrogenic systemic fibrosis in 6 kidney transplant recipients: A single-center experience

Abstract: Background: Nephrogenic systemic fibrosis (NSF) is a fibrotic disorder occurring in patients with renal dysfunction. Exposure to gadolinium (Gd)-based contrast agents (GBCAs) during renal impairment is associated with development of NSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The interval between GBCA exposure and NSF was available for 336 patients, ranging from the same day to approximately 10 years (median, 42 days; mode, 30 days; interquartile range, 19-90 days). For patients in whom GBCA dose was reported or could be estimated from the examination type, 6.7% (19 of 282) of patients were administered a standard dose (0.1 mmol/kg) or lower, and 93.3% (263 of 282) (23). Another patient in the same study improved by switching from subcutaneous administration of darbepoetin to intravenous administration of darbepoetin.…”
Section: Type Of Mri-mri Examination Typementioning
confidence: 99%
“…The interval between GBCA exposure and NSF was available for 336 patients, ranging from the same day to approximately 10 years (median, 42 days; mode, 30 days; interquartile range, 19-90 days). For patients in whom GBCA dose was reported or could be estimated from the examination type, 6.7% (19 of 282) of patients were administered a standard dose (0.1 mmol/kg) or lower, and 93.3% (263 of 282) (23). Another patient in the same study improved by switching from subcutaneous administration of darbepoetin to intravenous administration of darbepoetin.…”
Section: Type Of Mri-mri Examination Typementioning
confidence: 99%
“…They also reported that patients with renal disease, who were exposed to gadolinium‐containing contrast agents and developed NSF, were acidotic at the time of imaging, while those who did not develop NSF were not. NSF can also develop in kidney transplant recipients with altered graft function . Marckmann et al studied 13 cases of NSF and calculated an odds ratio of 32.5 (95% confidence interval 1.9–549.2; p < 0.0001) for development of NSF after exposure to gadodiamide.…”
mentioning
confidence: 99%
“…Definitive diagnosis of NSF requires deep skin biopsy and histopathological examination. A recently published study by Lemy et al showed that of 33 patients with kidney transplant exposed to Gd-CM, five (15.2%) developed NSF [47]. The relative risk for NSF development in patients with endstage renal disease (ESRD) in those who underwent gadolinium-enhanced MRI compared with those who did not was recently reported to be 44.74 [48].…”
Section: Discussionmentioning
confidence: 99%